ANALISIS KINERJA BETON ASPAL BERBAHAN TAMBAH LIMBAH BOTOL AIR MINERAL (PET) TERHADAP VARIASI TEMPERATUR DAN LAMA PERENDAMAN BANJIR - EVA AZHRA LATIFA; EDY PRAMONO (Politeknik Negeri Jakarta, 2014)
Roads with flexible pavements whose surface layer consists of asphalt concrete have a high likelihood to get deteriorate due to frequent submersion caused by floods. This research aims to attain an economical asphalt concrete mix with high durability to submersion under the influence of high temperature. Performance is improved by making the asphalt concrete mix resistant to temperature changes through adding mineral water bottle wastes into asphalt until the optimum characteristics are attained. The filler aggregate used is stone ash. Research is conducted on the asphalt concrete mixture that submerged for 24.72 and 120 hours at 300, 380, and 500 celsius. Stability, flow, marshall quotient and pore contents are all tested by the marshall method. . Determination of the best mix with soaking time and temperature variation is done by the regression analysis method. Keywords: aggregate filer, asphalt concrete, mineral water bottle waste, submersion, stability, temperature.